PERSEPSI MAHASISWA TERHADAP GENDER EQUALITY - Astuty, Delfriana Ayu (Pusat Studi Gender UIN Maulana Malik Ibrahim Malang, 2024)
Abstract Gender equality is one of the modern paradigms as an effort to create the concept of social justice for all individuals in various fields, including the realisation of the concept of justice for all students, both men and women on campus. Access to information, freedom and participation in every activity, supervision/control of existing policies and the benefits/impact of openness are 4 main indicators in realising gender equality. Perception is a process that occurs in an individual in terms of selecting, organising and translating suggestions, information, in order to form a pattern / picture that has meaning. This study aims to determine how students perceive gender equality. The research method used is descriptive analytic with a cross sectional approach. Based on the analysis that has been done, the majority of respondents' perceptions of gender equality are in the good category, namely 208 people (76.7%) and 63 people (23.3%) in the moderate category and based on the knowledge and attitudes of respondents about gender equality, the majority are in the good category located in the information access indicator, namely 262 people (96.6%), then moderately located in the indicator of the benefits of openness, namely 20 people (7.4%). The results of this study are expected to improve students' perceptions and understanding and contribute to the formulation of policies related to gender equality in higher education. Keywords: Perception; Student; Gender EqualityAbstrak Kesetaraan gender merupakan salah satu paradigma modern sebagai upaya mewujudkan konsep keadilan sosial bagi seluruh individu dalam berbagai bidang, termasuk terwujudnya konsep keadilan bagi seluruh mahasiswa, baik laki-laki maupun perempuan di lingkungan kampus. Akses informasi, kebebasan dan partisipasi dalam setiap kegiatan, pengawasan/kontrol terhadap kebijakan yang ada dan manfaat/dampak dari keterbukaan merupakan 4 indikator utama dalam mewujudkan kesetaraan gender. Persepsi merupakan suatu proses yang terjadi pada diri individu dalam hal menyeleksi, mengorganisasikan dan menerjemahkan saran-saran, informasi, sehingga membentuk suatu pola/gambaran yang memiliki arti. Penelitian ini bertujuan untuk mengetahui bagaimana persepsi mahasiswa terhadap kesetaraan gender. Metode penelitian yang digunakan adalah deskriptif analitik dengan pendekatan cross sectional. Berdasarkan analisis yang telah dilakukan, mayoritas persepsi responden tentang kesetaraan gender berada pada kategori baik yaitu sebanyak 208 orang (76,7%) dan 63 orang (23,3%) pada kategori cukup dan berdasarkan pengetahuan dan sikap responden tentang kesetaraan gender mayoritas berada pada kategori baik terletak pada indikator akses informasi yaitu sebanyak 262 orang (96,6%), kemudian cukup terletak pada indikator manfaat keterbukaan yaitu sebanyak 20 orang (7,4%). Hasil penelitian ini diharapkan dapat meningkatkan persepsi dan pemahaman mahasiswa serta memberikan kontribusi dalam perumusan kebijakan terkait kesetaraan gender di perguruan tinggi. Kata Kunci: Persepsi; Mahasiswa; Kesetaraan Gender